Pollen morphology of Rosales from Brazilian forest fragments of Cerrado - de Paula Cerdan, Isaura [UNESP] (2024)
Rosales, a well-supported order of angiosperms encompassing heterogeneous plants, holds significant representation in Brazilian territory, particularly Cerrado regions. These areas are susceptible to human impact. In this context, pollen data is vital in supporting taxonomic and ecological studies for species preservation. We analyzed pollen grains from 15 native Rosales species found in Brazilian Cerrado forest fragments belonging to the Cannabaceae, Moraceae, Rhamnaceae, and Rosaceae families using light and scanning electron microscopy. The pollen grains underwent acetolysis, qualitative description, and measurements, with statistical analysis, including multivariate methods, applied to quantitative data. Qualitative findings were organized for pollen description and multivariate cluster analysis. Our observations revealed pollen grains in monads, isopolar, small to medium, with subcircular, circular, or subtriangular amb, and suboblate, oblate-spheroidal, or prolate-spheroidal. Apertures include 2–3-porate, 3-colpate, or 3-colporate, with long or short ectoapertures, lalongate or circular endoapertures. The exine is thin, microreticulate, psilate-perforate, microgranulate, nanoechinate, or striate ornamentation, with the sexine thicker than the nexine. The key characteristics distinguishing families are number, type of apertures, and exine ornamentation. Quantitative data (length and width of ectoapertures, equatorial diameter in polar view, and polar diameter in equatorial view) contribute to the understanding of the palynology of Rosales from forest fragments, as these characteristics allow us to identify species or groups of species. Our findings confirm Rosales as eurypalinous, while the genera analyzed demonstrate stenopalynous traits. The qualitative and quantitative characteristics of pollen identified here expand the morphological knowledge of the species and can be used to understand the relationship among them.